OPTIMIZATION OF ANTERIOR CHAMBER ANGLE IMAGING APPROACH USING ANTERIOR OPTICAL COHERENCE TOMOGRAPHY IN GLAUCOMA (REVIEW ARTICLE) - Bilalov E.N.; Narziqulova Q.I.; Zakirkhojayev R.А.; Egamberdiyeva М.E.; Oralov B.А.; Gofurov А.U. (Western European Studies, 2024)
Glaucoma remains one of the leading causes of irreversible blindness worldwide, posing a significant threat to eye health. The most important aspect in managing glaucoma is early diagnosis and monitoring of the disease to prevent disease progression and vision loss. In recent years, significant advances in diagnostics have been made with the introduction of anterior optical coherence tomography (AOCT), which provides highly accurate visual representation of the anterior chamber angle and structures of the anterior segment of the eye. This method has become an important tool in the evaluation of patients with glaucoma, allowing the degree of angle closure to be determined and timely measures to be taken to prevent progression of the disease
Keywords: prevent; method; segment; measures